Respuesta :

Answer:

-26

Step-by-step explanation:

-4(-2)^2 + 2(-2) - 6

-4(4) + -4 - 6

-16 -10

-26

The value of equation [tex]-4x^{2}+2x-6[/tex] is -26 when x = -2

What is equation?

"An equation is a statement of equality between two expressions consisting of variables and/or numbers."

Substitute the value x = -2 in the given equation

[tex]=-4(-2)^{2}+2(-2)-6 \\=-4(4)-4-6\\=-16-4-6\\=-16-10\\=-26[/tex]

Hence, the value of the given equation is -26

To learn more about equation here

https://brainly.com/question/12263808

#SPJ2